Phase 1 study of chidamide in combination with venetoclax, azacitidine, aclarubicin, cytarabine and G-CSF for refractory/relapsed acute myeloid leukemia: clinical safety, efficacy, and correlative analysis - Wen, Yanan; Yang, Jingjing; Zhang, Xiawei; Liu, Qingyang; Gao, Wenjing; Dong, Lili; Zhao, Weijia; Huang, Sai; Liu, Daihong; Jing, Yu; Dou, Liping (Frontiers in Immunology, 2025)
BackgroundRelapsed or refractory AML (R/R-AML) remains a particularly adverse population necessitating improved therapeutic strategies. In this phase 1 study, we evaluated the efficacy and safety of chidamide, azacitidine, cytarabine, aclarubicin and granulocyte colony-stimulating factor (CACAG) in combination with the B cell lymphoma-2 inhibitor venetoclax (VEN) in R/R-AML.MethodsWe conducted a phase 1 trial to assess the safety and efficacy of CACAG-VEN regimen as a salvage induction regimen for patients with R/R AML. The primary endpoint was the treatment-related adverse events and overall response rate (ORR) following one cycle of the CACAG-VEN regimen. We also performed single-cell RNA sequencing on eight samples of bone marrow from four patients before and after CACAG-VEN treatment.ResultsFrom January 10, 2022, to June 8, 2024, the median follow-up was 461 days (range: 180–985 days). Thirty-four patients with refractory (n = 17) and relapsed (n = 17) AML were enrolled. The ORR was 76.5%, and the complete response rate was 73.5%. In patients with composite complete response (CRc), 44% of patients attained a measurable residual disease negative status, the 1-year overall survival (OS) rate was 82.3% (95% CI: 67.8–99.9%) and the progression-free survival rate (PFS) was 79.8%. After one cycle of CACAG-VEN, 44.1% (n = 15) of patients developed grade 3–4 myelosuppression. The median durations of neutropenia and thrombocytopenia were 17 days (95% CI: 15–22 days) and 24 days (95% CI: 22–41 days), respectively. Single-cell RNA sequencing revealed that post-treatment downregulation of MCL1, HIF1A, and ABCC1, highlighting the multi-targeted action of the regimen. Furthermore, treatment response was associated with the suppression of mitochondrial activity and the activation of the p53 signaling pathway.ConclusionIn patients with R/R AML, the CACAG-VEN regimen resulted in significant clinical benefits, with a high CRc rate and encouraging survival, as well as being well tolerated.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier, ChiCTR2200065634